2001
DOI: 10.1007/bf02287461
|View full text |Cite
|
Sign up to set email alerts
|

Organizational context and provider perception as determinants of mental health service use

Abstract: This study refines and tests an individual client model of service use and contrasts it with a model of service provision based on gateway provider perspectives. Structural equation models demonstrate that provider variables account for more service use variation than client variables. The client model accounts for 24% of the variance in service use, while the provider model accounts for 55% of the variance. Youth self-reported mental health was not positively associated with increased services or with provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 67 publications
1
37
0
Order By: Relevance
“…Our sample size of youth and PCPs was similar to previous investigations of identification (Costello et al, 1988;Chang et al, 1990;Stiffman, 2001). However, we should note that the clustered design of our data and the application of the random effects model limit the power to detect significant differences in proportions.…”
Section: Discussionsupporting
confidence: 52%
“…Our sample size of youth and PCPs was similar to previous investigations of identification (Costello et al, 1988;Chang et al, 1990;Stiffman, 2001). However, we should note that the clustered design of our data and the application of the random effects model limit the power to detect significant differences in proportions.…”
Section: Discussionsupporting
confidence: 52%
“…In this retrospective study of youth suicide deaths, well-established risk factors including the expression of suicidal thoughts were identifiable in most cases as warning signs of impending self-injurious behavior (CDC-MMWR, 2004). The rationale for teaching staff about mental health services also is supported by evidence that adults with knowledge of services more frequently direct youths to treatment (Stiffman et al, 2001). According to the surveillance model, gatekeeper training should have a relatively comparable impact across trained staff, in which case modest increases in knowledge and attitudes could raise exponentially the overall rate of referrals of suicidal youths in a school (Brown et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that predisposing and enabling categories generally had low relative importance in the utilization of these services. Although the health care landscape has changed during the past thirty three years many studies still find that need mediates the influence of predisposing and enabling factors on service use (Stiffman et al, 2001). …”
Section: Needmentioning
confidence: 99%
“…Despite their role as the first and often only interaction for a vulnerable patient within a health care system, primary care providers often do not accurately perceive patient needs (Stiffman et al, 2001;Taira et al, 1997) which can be a determinant of service access (Stiffman et al, 2000). Although such measures can be difficult to conceptualize during research design, the reduction of health disparities requires that we understand both the influences on service use and the gap between need and access (Stiffman et al, 2001).…”
Section: Needmentioning
confidence: 99%
See 1 more Smart Citation